Li2ZrO3 based Li-ion conductors doped with halide ions & sintered in oxygen-deficient atmosphere. Issue 22 (15th November 2021) - Yang, Lin; Li, Zhicheng; Gao, Caiyun; Gong, Shen; Chen, Jiahao; Chen, Hongzhu; Zhang, Hong
Abstract: All-solid-state batteries have recently attracted much attention for their high energy density and safety. Li2 ZrO3 -based Li-ion conductors with high electrochemical stability have potential applications for electrolytes in all-solid-state batteries. In this work, comparative investigations of Li2 ZrO3 and halogen doped Li2 ZrO3 ceramics were conducted by sintering at 700 °C in air or in oxygen-deficient atmosphere which was induced by a simple setup covering with corundum crucible. The analysis of phase composition reveals that the undoped Li2 ZrO3 ceramic sintered in air contains pure monoclinic phase, while halogen-doped Li2 ZrO3 sintered in air and all ceramics sintered in oxygen-deficient atmosphere are simultaneously composed of monoclinic and tetragonal phases. Li2 ZrO3 ceramic with tetragonal phases has higher conductivity (0.28 mS cm −1 for undoped Li2 ZrO3 ) than the pure monoclinic Li2 ZrO3 (0.07 mS cm −1 ), and halogen doping can further enhance the conductivity of Li2 ZrO3 ceramics higher than 0.5 mS cm −1 at room temperature.